133k views
1 vote
1/3 x− 1/8 y=3
7y+9x=−2
please solve the system
45 points for who does

User Jian
by
5.1k points

1 Answer

0 votes

Answer:


x=6\\y=-8

Explanation:


(1)/(3)x-(1)/(8)y=3\\ 7y+9x=-2

One method could be rewriting the second equation as x in terms of y and solving by replacing in the first equation.


7y+9x=-2\\9x=-2-7y\\x=(-7y-2)/(9)

Replace...


(1)/(3)x-(1)/(8)y=3


(1)/(3)((-7y-2)/(9))-(1)/(8)y=3


(-7y-2)/(27)-(1)/(8)y=3


-(7)/(27)y-(2)/(27)-(1)/(8)y=3

add
(2)/(27) on both sides.


-(7)/(27)y-(1)/(8)y=3+(2)/(27)

Combine like terms


((-7)(8)-(1)(27))/((27)(8)) y=((3)(27)+2)/(27)


(-56-27)/(216) y=(81+2)/(27)


(-83)/(216)y =(83)/(27)

Now, to get rid of the fraction and isolate y, multiply by the reciprocal or the inverted fraction.


((216)/(-83)) (-83)/(216)y =(83)/(27)((216)/(-83))


y=(216)/(-27)

Simplify


y=-8

Now replace the value of y in either equation to find x.


7y+9x=-2\\7(-8)+9x=-2\\-56+9x=-2

add 56


56-56+9x=-2+56\\9x=54\\

Divide by 9


(9x)/(9)=(54)/(9)\\ x=6

To check whether these values are accurate, replace in either equation both values and you should have an equality. In this case I'll do it in both equations.


(1)/(3)x-(1)/(8)y=3


(1)/(3)(6)-(1)/(8)(-8)=3


2-(-1)=3\\2+1=3\\3=3

-----------------------------------------------------------------


7y+9x=-2\\7(-8)+9(6)=-2\\-56+54=-2\\-2=-2

User David Carmo
by
5.1k points